Stairs Designed for People with Special Needs - Tedi Kurniawan (Indonesian Journal of Community and Special Needs Education, 2022)
The purpose of this paper is to explain the standard for stairs for people with special needs. This study was based on a literature review from various sources, particularly sources in Indonesia. Detailed examples on how to design stairs were presented. This study is hopefully used as a reference and a guide for architectural and environmental construction, particularly in hospitals, schools, and public facilities for people with special needs (i.e. wheelchairs, crutches, and canes for the blind).